2011
DOI: 10.3892/mmr.2011.667
|View full text |Cite
|
Sign up to set email alerts
|

TUNEL-positive cells in the surgical border of an amputation due to infected diabetic foot

Abstract: Abstract. Diabetic infected foot is the outcome of progressive vascular and neurological damage caused by persistent chronic hyperglycemia. Due to acute hypoxia and infection, the tissues develop extensive necrosis and gangrene, which often require amputation. The decision regarding the level of amputation relies mainly on the personal experience of the surgeon who must identify the healthy tissue without necrosis. However, tissue cells under stress may succumb before clear evidence of necrosis is present. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…In the present study, the combination of FA-chitosan/mIP-10 and FC vaccine significantly reduced the number of Ki67 + tumor cells but increased the number of apoptotic cells in the tumor tissues which was consistent with the previous reports 31, 32, 33. These data suggest that Th1 and CTL cells induced by combination therapy inhibit the proliferation of tumor cells and trigger apoptosis by direct cell-cell contact or indirectly by soluble mediators.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the combination of FA-chitosan/mIP-10 and FC vaccine significantly reduced the number of Ki67 + tumor cells but increased the number of apoptotic cells in the tumor tissues which was consistent with the previous reports 31, 32, 33. These data suggest that Th1 and CTL cells induced by combination therapy inhibit the proliferation of tumor cells and trigger apoptosis by direct cell-cell contact or indirectly by soluble mediators.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, diabetic hostderived MSCs have been partially impaired in biological function and reduced ability for promoting wound healing [25]. In previous studies, we also confirmed that diabetic host-derived hADSCs have impaired healing capacity compared with normal hADSCs [26]. Thus, extensive preclinical studies aimed at increasing stem cell viability are needed for developing more effective approaches to regeneration therapy using hADSC transplantation.…”
Section: Introductionsupporting
confidence: 74%
“…The procedures were approved by the Ethics Committee at the Affiliated hospital of Zunyi Medical University, with patient consent obtained before the procedure. hADSCs were isolated as previously described [26]. Briefly, the adipose tissue was minced, washed, and digested with 0.075% collagenase type I (Sigma, St. Louis, MO, USA) for 45 min in a shaker incubator at 37°C.…”
Section: Cell Culturementioning
confidence: 99%
“…Diabetic patients often suffer from both microvascular and macrovascular disease caused by ischemia and hypoxia [ 35 37 ]. A long-term hyperglycemic microenvironment in diabetes leads to microvascular cell loss and blood flow abnormalities.…”
Section: Discussionmentioning
confidence: 99%